Analysis of Economic Welfare on Mental Health From an Islamic Economic Perspective - Deddy Ibrahim Rauf; Hery Maulana Arif; Resky Amalia Hamka (PT Maju Malaqbi Makkarana, 2023)
This study aims to analyze whether there is a relationship between economic well-being and mental health when viewed from the perspective of Islamic economics, which is based on QS. Al-Quraish verses 3-4 have clearly shown that Islamic economics includes non-material or spiritual factors that are not present in the conventional view. The results of this study indicate that: 1) in Islam success is not only about wealth or material things, it can be in the form of physical and mental health and (spiritual) peace of mind that arises because of monotheism, 2) fulfillment of one's consumption needs can also be one of the indicators that can keep a person's mental health maintained, 3) Each individual has their own anxieties, and the solution for them to overcome their fears and anxieties to continue to obtain spiritual well-being in life in general is to return to the values of monotheism or beliefs mentioned in the welfare indicator the first Islamic economy and it turns out that each of these indicators synergizes with each other.